SYSTEMS DIFFERENTIAL INEQUALITIES WITH ONE-SIDE LIPSCHITZ RIGHT PARTS - Копач, Михайло Іванович; Обшта, Анатолій Феліксович; Обшта, Богдан Антонович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Some theorems on two-side estimations of solutions of ordinary differential equations systems with weaker than the Lipschitz conditions assumptions are established.